Genes and environment in attachment. (May 2020) - Picardi, Angelo; Giuliani, Eugenia; Gigantesco, Antonella
Highlights: Both genes and environment contribute to individual differences in attachment. In childhood, important role of the shared environment, might decrease over time. In adulthood, genetic factors may have increasingly greater influence. Considerable influence of unshared environment throughout the life cycle. The findings of molecular genetic studies are suggestive but, overall, inconclusive. Abstract: In the last two decades, there has been increasing research interest in disentangling the contribution of genetic and environmental factors to individual differences in attachment, and in identifying the genes involved in shaping attachment. Twin studies suggest that as attachment changes during the course of development, genetic factors may play a progressively more important role, while shared environmental effects might decrease. However, most of this literature is limited by low power, measurement issues, and cross-sectional design. The findings of molecular genetic studies are, overall, inconclusive. The literature on main genetic effects and gene-by-environment interactions on attachment is filled with inconsistent and unreplicated findings. Also, most studies are underpowered. Challenges for future research are to identify the unshared environmental mechanisms involved in shaping attachment, and to better elucidate the genes involved and their interaction with the environment. Some pioneer studies suggested that the incorporation of epigenetic processes into G × E interaction models might represent a promising future way for investigating the complex, dynamic interplay between genes, environment, and attachment.